2010
DOI: 10.1016/j.phpro.2010.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Two-state protein-like folding of a homopolymer chain

Abstract: Many small proteins fold via a first-order "all-or-none" transition directly from an expanded coil to a compact native state. Here we study an analogous direct freezing transition from an expanded coil to a compact crystallite for a simple flexible homopolymer. Wang-Landau sampling is used to construct the 1D density of states for square-well chains of length 128. Analysis within both the micro-canonical and canonical ensembles shows that, for a chain with sufficiently short-range interactions, the usual polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Our first result from analyzing the TSE is an observation made earlier by Taylor, Paul, and Binder 2 for the pure square-well chain: typical transition states consist of a crystalline nucleus with one or more chain fragments attached to it. The result of Taylor et al 7 was drawn from a visual inspection of states which are energetically in between the high-energy coil and the low-energy crystalline phase. Our committor analysis confirms this observation with a more rigorous approach.…”
Section: Committor Analysis and Transition State Ensemblementioning
confidence: 99%
See 2 more Smart Citations
“…Our first result from analyzing the TSE is an observation made earlier by Taylor, Paul, and Binder 2 for the pure square-well chain: typical transition states consist of a crystalline nucleus with one or more chain fragments attached to it. The result of Taylor et al 7 was drawn from a visual inspection of states which are energetically in between the high-energy coil and the low-energy crystalline phase. Our committor analysis confirms this observation with a more rigorous approach.…”
Section: Committor Analysis and Transition State Ensemblementioning
confidence: 99%
“…This is indicative of the rough and diffusive nature of the freezing transition. From a two-dimensional free energy landscape as a function of the total energy U and the squared radius of gyration R 2 g , Taylor et al 7 identified the dominant folding pathway as the minimum free energy path. Our results strongly suggest that such a dominant folding pathway is only representative in an average sense, especially regarding the squared radius of gyration.…”
Section: Committor Analysis and Transition State Ensemblementioning
confidence: 99%
See 1 more Smart Citation
“…The present all-or-none model predicts a sharpening of the heat capacity spike in C v (T ) versus T as the number of F bonds increases 12 and it predicts that the transition temperature is independent of chain length for long chains, assuming that each added bead has the same number of F-bonds per bead as the previous bead. Simulations find evidence of a single spike in C v (T * ) versus T * as the interaction range /b decreases below 0.1, which is probably the upper bound for .…”
Section: Discussionmentioning
confidence: 67%
“…Our interest in the collapse problem originated from the works of Taylor et al [10][11][12] who investigated the all-or-none a) Electronic mail: glenn.evans@oregonstate.edu. transition from an expanded coil to a compact state for a freely jointed chain with SW nonbonded interactions.…”
Section: Introductionmentioning
confidence: 99%